Effects of cerium oxide nanoparticles on differentiated/undifferentiated human intestinal Caco-2 cells. (1st March 2018) - Vila, Laura; García-Rodríguez, Alba; Cortés, Constanza; Velázquez, Antonia; Xamena, Noel; Sampayo-Reyes, Adriana; Marcos, Ricard; Hernández, Alba
Abstract: Since ingestion constitute one of the main routes of nanoparticles (NPs) exposure, intestinal cells seems to be a suitable choice to evaluate their potential harmful effects. Caco-2 cells, derived from a human colon adenocarcinoma, have the ability to differentiate forming consistent cell monolayer structures. For these reasons Caco-2 cells, both in their undifferentiated or differentiated state, are extendedly used. We have used well-structured monolayers of differentiated Caco-2 cells, as a model of intestinal barrier, to evaluate potential harmful effects associated to CeO2 NPs exposure via ingestion. Different parameters such as cell toxicity, monolayer integrity and permeability, cell internalization, translocation through the monolayer, and induction of DNA damage were evaluated. No toxic effects of CeO2 NPs were observed, independently of the differentiated state of the Caco-2 cells. In the same way, no effects on the monolayer integrity/permeability were observed. Although important cell uptake was demonstrated in undifferentiated cells (by using confocal microscopy), CeO2 NPs remained mostly attached to the apical membrane in the differentiated cells. In spite of this apparent lack of uptake in differentiated cells, translocation of CeO2 NPs to the basolateral chamber was observed by using confocal microscopy. Finally no genotoxic effects were observed when the comet assay was used, although decreases in the levels of oxidized bases were observed, supporting the antioxidant role of CeO2 NPs. Highlights: CeO2 NPs uptake differed between differentiated and undifferentiated cells. CeO2 NPs were non-toxic, independently of the differentiation stage. No significant changes in the integrity of the monolayer were observed. The monolayer acted as a true barrier, allowing only a low CeO2 NPs translocation. Non-genotoxic effects were observed, when the comet assay was used.